Diversity and distribution of Phanaeini (Coleoptera: Scarabaeidae: Scarabaeinae) in Mexico - Lizardo, Viridiana; Escobar, Federico; Rojas-Soto, Octavio (Zootaxa, 2017)
In this study, we systematized available distribution data, obtained from biological databases and relevant literature, for Mexican species belonging to the tribe Phanaeini. The main objectives were to provide an overall description of the distribution records in biological collections, to detect potential sampling biases, to describe the seasonality of collections and to obtain species distribution models using the Desktop GARP algorithm. A total of 5,562 records, corresponding to 32 species in Mexico, were compiled, including the recently described Phanaeus zoque Moctezuma & Halffter, 2017. This compilation includes 784 unique collection records at 325 localities. These records were mainly distributed along the Trans-Mexican Volcanic Belt, the Sierra Madre Oriental and Sierra Madre Occidental mountain ranges and throughout the states of Chiapas and Veracruz. The Mexican High Plateau, the state of Tlaxcala and the Yucatan Peninsula are lacking in records. Distribution maps were created for species of three genera (Phanaeus MacLeay, 1819, Coprophanaeus Olsoufieff, 1924, and Sulcophanaeus Olsoufieff, 1924) and for 29 species present in Mexico. These species distributions are largely delimited by geomorphological features and vegetation types and coincide with expert descriptions of this tribe; some species show expanded distribution ranges. These maps provide a starting point for further analyses, the planning of future field studies, and the verification of possible new species in the Mexican territory.